Calcium and calmodulin modulate fungal spore germination - and U.P. SINGH, B. PRITHIVlRAJ, K. MANDAL (Indian Phytopathology, 2002)
The effect of verapamil (a plasma membrane Ca2+ channel blocker), ruthenium red (RR) (an organelle Ca2+ channel blocker) and chlorpromazine, a calmodulin (CaM) antagonist was investigated on the spore germination of some plant pathogenic fungi (Fusarium udum, F. oxysporum f.sp. ciceris, Curvularia lunata [Cochliobolus lunatus], Alternaria brassicicola and Colletotrichum capsici). The Ca2+ channel blockers and CaM differentially affected spore germination. The inhibitory effect of Ca2+ reverted by increasing the external Ca2+ concentration. Fungi sensitive to verapamil were relatively tolerant of RR and vice-versa. Washing spores with ethylene diamine tetra acetic acid (EDTA) increased sensitivity to Ca2+ channel blocker. It is suggested that there is an interplay of cell wall and organelle Ca2+ in triggering the spore germination process.